Understanding University Students' Use of ChatGPT in the English Writing Process: A Qualitative Inquiry - Rian Erlangga; Ratna Andhika Mahaputri; Haris Budiana (Journal of Educational Management Research, 2026)
This study aimed to investigate how university students use ChatGPT throughout the English writing process and how AI-assisted interaction influences their writing revisions. Using a qualitative inquiry, the study involved 30 university students who had used ChatGPT for English writing tasks at least three times. Data were collected asynchronously through pre- and post-ChatGPT writing drafts, structured reflection journals, prompt logs, and written follow-up responses from selected participants, and were analyzed thematically with triangulation to enhance trustworthiness. The findings revealed that students mainly used ChatGPT during the revising and editing stages rather than for idea generation. They engaged critically with AI-generated suggestions by selectively accepting or modifying them to preserve their own voice, examples, and contextual relevance. Draft comparisons showed an average increase of 14.3% in essay length, along with more developed sentences and conclusions, reflecting improvements in grammar, vocabulary, and organization. These findings suggest that ChatGPT functions as a supportive revision tool rather than a replacement for students' writing and provide implications for integrating generative AI into English writing instruction while promoting AI literacy and responsible AI use in higher education.